Clinical case of senesto-hypochondrical form of schizophrenia with implementation of pathological bodily sensations mainly in the orofacial area: problems of differential diagnosis at the early stages - Ekaterina D. Kochereva; Larisa S. Dzikovitskaya; Marina V. Kozlova; Vlada V. Titova; Marina A. Samushiya (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The article presents a clinical case of the senesto-hypochondriacal form of schizophrenia, the implementation of violations of bodily perception within which for a long time was limited to the orofacial space against the background of orthodontic pathology. Prosopalgia is a transnosological syndrome characteristic of a heterogeneous group of disorders, the differential diagnosis of which, due to the peculiarities of the innervation of the facial area, can be difficult and requires special attention for the timely determination of their nosological affiliation and the initiation of adequate therapy. Interest in the clinical case is due to longlasting senestoalgic syndrome, similar in clinical picture to established pathology of the temporomandibular joint, which complicated the timely assessment of the patient’s condition and led to exacerbation of the mental disorder in the absence of psychopharmacological therapy. The article provides an analysis of the place of mental pathology in the formation and development of orofacial pain, both of a somatogenic nature and in the context of somatopsychic disorders, emphasizing the need for a comprehensive assessment of both the dental and mental status of such patients in order to formulate optimal approaches to treatment.